Bosnian studies : perspectives from an emerging field - Karabegović, Dženeta; Karamehić-Oates, Adna (University of Missouri Press, 2022)
"The diverse entry points of scholars in their questions and research related to Bosnia and Herzegovina, the war and its aftermath suggest that 'Bosnian Studies' is an emerging field, encompassing the aforementioned approaches to research and study. The ambition of this coedited volume is therefore to not only examine the emergence of 'Bosnian Studies' as a field through the individual chapters of scholars in different disciplines, but also to highlight how diaspora scholars in particular are contributing to the field's dynamism and trends"--